2020
DOI: 10.3390/microorganisms8121893
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Mediated Microbial “Gardening” Capacity of a Seaweed Holobiont Is Dynamic

Abstract: Terrestrial plants are known to “garden” the microbiota of their rhizosphere via released metabolites (that can attract beneficial microbes and deter pathogenic microbes). Such a “gardening” capacity is also known to be dynamic in plants. Although microbial “gardening” has been recently demonstrated for seaweeds, we do not know whether this capacity is a dynamic property in any aquatic flora like in terrestrial plants. Here, we tested the dynamic microbial “gardening” capacity of seaweeds using the model invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Many host or environmental factors were not measured in this study but may also significantly influence microbial communities, such as secretion of specific carbohydrates and proteins (Lachnit et al, 2011; Steinberg and De Nys, 2002), antimicrobial secondary metabolites or differences in photosynthetic yield (which indeed varied across populations). Future studies comparing genetic measures identified here with more localized chemical and isotopic signatures of the hosts may reveal other drivers of host‐associated microbiota (e.g., Bengtsson et al, 2011; Saha et al, 2020; Weigel and Pfister, 2021). Finally, surface‐associated microbial communities can vary between thallus regions (Ihua et al, 2020) and also can change dramatically over the course of development in many organisms (McFall‐Ngai et al, 2013; Yatsunenko et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Many host or environmental factors were not measured in this study but may also significantly influence microbial communities, such as secretion of specific carbohydrates and proteins (Lachnit et al, 2011; Steinberg and De Nys, 2002), antimicrobial secondary metabolites or differences in photosynthetic yield (which indeed varied across populations). Future studies comparing genetic measures identified here with more localized chemical and isotopic signatures of the hosts may reveal other drivers of host‐associated microbiota (e.g., Bengtsson et al, 2011; Saha et al, 2020; Weigel and Pfister, 2021). Finally, surface‐associated microbial communities can vary between thallus regions (Ihua et al, 2020) and also can change dramatically over the course of development in many organisms (McFall‐Ngai et al, 2013; Yatsunenko et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Phenotypic variation was high at this site, particularly for morphological characteristics and levels of grazing (see Figure host or environmental factors were not measured in this study but may also significantly influence microbial communities, such as secretion of specific carbohydrates and proteins (Lachnit et al, 2011;Steinberg and De Nys, 2002), antimicrobial secondary metabolites or differences in photosynthetic yield (which indeed varied across populations). Future studies comparing genetic measures identified here with more localized chemical and isotopic signatures of the hosts may reveal other drivers of host-associated microbiota (e.g., Bengtsson et al, 2011;Saha et al, 2020;Weigel and Pfister, 2021).…”
Section: Phenotypic Associations With Microbial Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroalgae and their epiphytic bacteria interact as a functional entity, and their interactions can improve seaweed health, growth, disease suppression and adaptation to environmental stressors (Egan et al ., 2013 ; Schmidt and Saha, 2021 ). Chemical ‘gardening’ of protective microbes by seaweed has even been demonstrated, which in turn enhances the sustainable production of seaweeds (Saha and Weinberger, 2019 ; Saha et al ., 2020 ). Consequently, the associated increased seaweed biomass in the environment can be used for feeds, biofuels and fertilizers.…”
Section: Ecological Applicationsmentioning
confidence: 99%
“…Both micro and macroalgae are prone to pathogenic microbial and viral contamination (Zhu et al 2020;Behera et al 2022). It should be noted, however, that in some cases, "contaminating" microorganisms have been shown to function as symbionts that can improve algal growth and performance (Amaral et al 2013;Wichard 2022), and have even been shown to be "farmed" by seaweed to some extent (Saha et al 2020).…”
Section: Introductionmentioning
confidence: 99%